Reverse teaching as a methodological strategy for mathematics learning in higher education - Orcos, Lara; Cordero, Alicia; Jordán, Cristina; Magreñán, Á. Alberto; Sanabria, E.; Torregrosa, Juan Ramón (Nova Science Publishers, Inc., 2022)
The aim of this study is to assess the opinions of the first year students of the subject Discrete Mathematics of the degree of Big Data, at the Universitat Politècnica de Valencia (UPV) that have used flip methodology as a pedagogical approach to study the content of the subject. For this, it has been established a methodological approach based on the use of videos to enable the students to get the theoretical basis of the content to study. Classroom moments are transformed into spaces where students can work on practical aspects related to content enhancing meaningful learning. © 2020 Nova Science Publishers, Inc.
Es un capítulo del libro: L. Orcos, A. Cordero, C. Jordán, A. A. Magreñán, E. Sanabria and J. R. Torregrosa (2020), "Didactics of Mathematics: New Trends and Experiences": Reverse teaching as a methodological strategy for mathematics learning in higher education.
Keywords: discrete mathematics; flip learning; meaningful learning; university; Scopus(2)